PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN KEBAYORAN LAMA - Srito Ayu, Ritna; Sulaeman, Asep (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of job satisfaction and work discipline on employee performance in Kebayoran Lama Districh Office. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 60 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are job satisfaction has a significant effect on employee performance with a determination coefficient value of 42,7% and hypothesis testing obtained t count > t table or (7.424 > 2.002). Work discipline has a significant effect on employee performance with a determination coefficient value of 48.7% and hypothesis testing obtained t count > t table or (6.546 > 2.002). Job satisfaction and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 8.334 + 0.428X1 + 0.380X2. The coefficient of determination is 61,4% while the remaining 38,6% is influenced by other factors. Hypothesis testing obtained F count > F table or (45.384 > 2.770).